EVALUATION OF SERUM TOTAL, LIPID AND PROTEIN ASSOCIATED SIALIC ACIDS LEVELS AS AN INFLAMMATORY MARKERS IN TYPHOID FEVER PATIENTS
Total sialic acid (TSA) and its fraction lipid and protein associated sialic acids (LASA andPASA) were measured in serum belonged to 100 patients with typhoid fever, and 50 normalsubjects considered as normal healthy controls. Data analysis shows that the levels of TSA(91.58